2012
DOI: 10.5455/msm.2012.24.76-80
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Etiology and Several Socio-demographic Characteristics of Acute Poisoning in Children Treated in the Intensive Care Unit

Abstract: Aim:The aim of this work has been to present the frequency, etiology and several other socio-demographic characteristics of acute poisoning in children.The treated patients and methods of work:The treated patients were children of all age groups hospitalized in the Pediatric Clinic of Prishtina during year 2009. The study was done retrospectively. The diagnosis was done on the basis of heteroanamnesis and in several cases on the basis of the anamnesis data of a child, routine laboratory tests and toxicologic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
4
11
0
3
Order By: Relevance
“…Many studies listed analgesics and benzodiazepines as the most common drugs in childhood poisoning. [12,26,27] In the clinical profile of studied cases, we noticed that neurological manifestations were the commonest (39.4%) as: disturbed consciousness, convulsions or abnormal movements. Two patients spontaneously recovered a normal neurological condition within the first 24 hours without an antidote treatment.…”
Section: Esctj;vol(6) N0(1) June;2018mentioning
confidence: 89%
See 1 more Smart Citation
“…Many studies listed analgesics and benzodiazepines as the most common drugs in childhood poisoning. [12,26,27] In the clinical profile of studied cases, we noticed that neurological manifestations were the commonest (39.4%) as: disturbed consciousness, convulsions or abnormal movements. Two patients spontaneously recovered a normal neurological condition within the first 24 hours without an antidote treatment.…”
Section: Esctj;vol(6) N0(1) June;2018mentioning
confidence: 89%
“…[10] Other studies showed that the incidence was more common in boys. [11,12]. However, some reports showed that distribution is nearly equal in males and females.…”
Section: -7-mentioning
confidence: 99%
“…Childhood poisoning is a complicated condition resulting from interactive relations of the family, the child, the child's environment and the xenobiotic itself making it frequent [4]. In addition to economic and communities' health damage, childhood poisoning cases also result in an enormous emotional and psychological family load [5].…”
Section: Introductionmentioning
confidence: 99%
“…The observation of pharmaceutical products as a group being the commonest cause of childhood poisoning is reported by previous studies in Thailand (Chatsantiprapa et al, 2001), Saudi Arabia (Izuora and Adeoye, 2001), Pakistan (Aslam et al, 2002), England (Groom et al, 2006), Turkey (Sahin et al, 2011 andOzdemir et al, 2012), Greece (Tsalkidis et al, 2010), Kosovo (Azemi et al, 2012) and New Zealand (Fan et al, 2013).…”
Section: Discussionmentioning
confidence: 81%